The landscape of education “reform” in Chicago: Neoliberalism meets a grassroots movement - Lipman, Pauline (Education Policy Analysis Archives, 2017)
This article examines the dialectics of Chicago’s neoliberal education policies and the grassroots resistance that parents, teachers, and students have mounted against them. Grounding the analysis in racial capitalism and neoliberal urban restructuring, I discuss interconnections between neoliberal urban policy, racism, and education to clarify what is at stake for communities resisting Chicago’s policies. The paper describes deep and pervasive racial inequities, school closings, privatization, and disenfranchisement driving organized opposition and the labor-community alliance at the center of organized resistance. I argue that neoliberal education policy is racialized state violence, and education is a battleground for racial justice and Black self-determination. I conclude with observations on Chicago’s experience so far that might be useful in other contexts.